PEMAAFAN DAN KEBAHAGIAAN PADA LANSIA - Pusvitasari, Putri; Jayanti, Arini Mifti (JURNAL PSIKOLOGI INSIGHT, 2020)
The purpose of this research is to identify the relationship between forgiveness and happiness in elderly at Wredha Abiyoso Pakem Yogyakarta house. The subject are 30 seniors who live at the house. This research uses two scales, those are forgiveness scale which has 10 items and refers to Nashori (2011) and happiness scale which has 20 items and refers to seligman’s happiness scale (2005). The data analysis which is used in the research is product moment from pearson. The result shows that there is a significant relationship between forgiveness and happiness in the elderly who live in the Werdha Abiyoso Pakem Yogyakarta house. It is proven by correlation coefficient between forgiveness and happiness for 0,533 with p-value of 0,000 (p smaller than 0,01).